Synthesis and Crystal Structure of Novel Zinc Porphyrin ZnTCPP(H2O)·MeOH [TCPP = meso-tetra(4-carboxyphenyl)porphyrin] - Lin, Weisheng (Asian Journal of Chemistry, 2013)
In order to study new porphyrin complexes, a novel zinc porphyrin ZnTCPP(H2O)·MeOH [TCPP = meso-tetra(4-carboxyphenyl)porphyrin; MeOH = methanol] has been designed, prepared and characterized by a single-crystal X-ray diffraction method. The title complex crystallizes in the orthorhombic system with a Cmca space group with eight molecules per unit cell. Zinc porphyrin has an isolated structure in which the zinc ion coordinates to four Nporphyrin atoms and one Owater atoms.